WHAT LECTURERS ARE PAID FOR:AN ANALYSIS OF UNIVERSITIES’ LEGISLATIVE ACTS - Natalia V. Rodina (Высшее образование в России, 2016)
The article presents the analysis of lecturers’ performance indicators, which were listed in 70 universities’ legislative acts. These universities are subordinated to the Ministry of education and science of Russian Federation. It was shown by foreign researchers that the system of assessment used in education had an impact on the professional activities of teachers and lecturers. Such management decisions as promotion, punishment, control were used after these assessments. We have analyzed lecturers’ performance indicators from the standpoint that these indicators can influence the professional activity of the lecturer. The frequency of lecturers’ performance indicators among 70 universities’ legislative acts wascalculated. Results of research work, administrative positions and previous achievements of lecturers (such as scientific statuses (candidate and doctor of science, academicians and etc.) and awards in research and teaching) are largely rewarded in the universities.